The Mutual fund investment performance: Indonesia Sharia stock index as characteristics moderating model - Azis, Musdalifah; Darmalaksana, Dedy; Suryaningsi, Suryaningsi; Jaafar, Muhammad Sukar (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study investigates how the Sharia stock price index influences the relationship between various factors, such as the expense ratio, portfolio turnover ratio, cash ratio, age, size, and characteristics of Sharia mutual funds, and their overall performance. Methodology – This study employed a quantitative descriptive research method to analyze 316 populations. Purposive sampling was used to obtain a total of 51 samples. We used research tools for data collection and SMART PLS 4 statistical software to analyze the collected data. Findings – The characteristics of ISSI-moderated mutual funds have a significant positive effect on the performance of Sharia mutual funds. To achieve better performance, investment managers must incur high costs in implementing active strategies. The more active the investment manager is in trading by looking at existing opportunities, the better the performance of the Sharia Mutual Funds. Implications – The implications of this research indicate that the movement of the Sharia stock price index can strengthen the positive causal relationship between several characteristics of Sharia mutual funds. The effects of Sharia mutual fund portfolio instruments, including shares, bonds, and deposits from the Sharia banking industry, also contribute to improving the performance of Sharia mutual funds in Indonesia.Originality – This study investigates the moderating role of the Sharia stock price index on several characteristics of Sharia mutual funds, including the expense ratio, portfolio turnover ratio, cash ratio, age of the mutual funds, and size of the mutual funds, in relation to their performance.